Small square shrine near the entrance gateway of the Mahanaleshwar temple complex - Temples of India Project Team (Jio Institute, 2024)
A small square shrine is there near the pratoli (entrance gateway) of the western boundary of the Mahanaleshwar temple complex. The structure has a phamsana shikhara (pyramidical superstructure) on a square plan. It was probably built from donations received by pilgrims or in memory of some deceased soul. Several such small temples are scattered in the temple complex.